육성기 거세한우의 유지에너지 요구량 결정에 관한 연구 - 설용주; 김경훈; 백열창; 이상철; 옥지운; 이강연; 홍성구; 장선식; 최창원; 송만강; 이성실; 오영균; et al. (Journal of animal science and technology, 2011)
Present experiment was carried out to determine maintenance energy requirements for growing Hanwoo steers. Six Hanwoo steers (BW = $180.6{±}3.1$ kg) were used in two 3 ${×}$ 3 latin square design with three different energy intake levels; TDN 1.70 kg (Low), 2.05 kg (Medium), 2.80 kg (High), respectively, based on the Korean Feeding Standards. Each period lasted 18 days including a 14-day adaptation and a 4-day measuring period. The steers were in the head hood chamber system (one cattle per chamber) during each measuring time to measure heat and methane production for 1 day. Dry matter intake was 2,058, 3,256 and 3,881 g/day for Low, Medium and High TDN, respectively. Increase in energy intake did not affect digestibilities of dry matter, crude protein, crude fiber, crude fat, NDF, ADF and nitrogen-free extract. Gross energy intake averaged 180.21, 292.74 and 337.15 kcal/$BW^{0.75}$ for Low, Medium and High TDN, respectively. Energy loss was 28.7% in feces and 2.1% in urine of gross energy intake. Further, energy loss from methane produced during rumen fermentation was 6~8.3%, while body heat loss averaged 34~60%. Intercept of regression equation between ME intake and retained energy indicated that the energy requirement was 109.84 kcal ME/$BW^{0.75}$. 본 시험은 생후 6개월 령의 육성기 거세한우 6두($180.6{±}3.1$ kg)를 공시하여 옥수수 위주의 농후사료 60%와 티모시 건초 40% 비율로 급여하였고 TDN 함량은 71.4%, CP는 14.6%이었다. 시험은 Korean Feeding Standard for Hanwoo (2007)에 따라 일당 증체량 0 kg, 0.4 kg, 0.7 kg/일에 필요한 각각의 TDN 함량 1.70 kg (Low), 2.05 kg (Medium), 2.80 kg (High)의 공시사료를 섭취할 수 있도록 하는 duplicated 3 ${×}$ 3 Latin square design으로 수행하였다. 에너지 수준에 따른 급여사료는 전량 섭취하였고, 일반적으로 건물섭취량의 증가가 반추위 통과속도를 높이기 때문에 소화율이 낮아지지만 본 실험에서는 건물, 조단백질, 조지방, 조섬유의 소화율은 차이가 없었다 (P>0.05). 섭취 에너지 수준별 평균 대사 체중 당 총에너지 섭취량은 180.2, 292.7와 337.2 kcal/$BW^{0.75}$이었다(P<0.001). 처리구별 총 에너지섭취량이 증가하면서 분으로 손실된 에너지도 51.1에서 99.71kcal/$BW^{0.75}$로 유의적으로 증가함(P<0.001)에 따라 가소화에너지는 약 70%로 처리 간 차이가 없었다. 뇨로 손실된 에너지는 3.5에서 7.9 kcal/$BW^{0.75}$로 유의적으로 증가하였고(P<0.03), 반추위 발효과정에서 발생되는 메탄가스에 의한 에너지 손실도 15.0에서 20.5 kcal/$BW^{0.75}$로 증가하는 경향을 보였다(P=0.06). 체열에 의한 손실량은 수준별로 차이가 없었지만, 총에너지섭취량(GE)에 대한 비율은 60.4, 41.2와 34.1%로 에너지 섭취량이 높아질수록 감소하였다. 대사에너지 섭취량 수준 110.6, 186.3, 209.1 kcal/$BW^{0.75}$와 각각의 체 축적 에너지 1.67, 65.76, 94.25 kcal/$BW^{0.75}$의 관계식을 통해 구한 X축 절편 값, 즉 유지를 위한 에너지 요구량은 109.8 kcal/$BW^{0.75}$로 나타났다.